Atlas of abdominal wall reconstruction - Rosen, Michael J., MD (Elsevier/Saunders, 2012)
Offers comprehensive coverage on a range of abdominal wall reconstruction and hernia repair. This title provides the guidance you need to make the most effective use of both commonly performed and new surgical techniques for abdominal wall reconstruction.